Health Disparities in General Medicine: A Systematic Review of Socioeconomic and Demographic Influences - Alsaiari , Saleh Aeidhah Saleh; alsaiari , Abdullah Saeed fraj; Shamlan, Ali Mohammed Tayyib; Al Fataih, Jaber Ali N; Alsayari , Saleh Mohammed Awad; Alshihe, Salim Hadi Mahdi; Allajam, Abdullah Hussein Saleh; Hasan, Mesfr Mohamad Alfarj; Al zarar, Yousef Mohammed Nasser; Alzarar, Ibrahim Mohammed Nasser (Journal of Ecohumanism, 2024)
Health disparities in general medicine are a critical concern, with socioeconomic and demographic factors such as income, education, race, gender, and geographic location contributing to unequal healthcare access, quality, and outcomes. This systematic review aims to assess how these factors influence health disparities in general medical settings. A comprehensive search was conducted across PubMed, Embase, and MEDLINE, focusing on studies published in the last decade that examined the role of socioeconomic and demographic variables in health outcomes within general healthcare. Forty studies met the inclusion criteria, including cohort and cross-sectional studies. Findings reveal significant health disparities associated with lower socioeconomic status, with low-income individuals facing higher morbidity and mortality risks and reduced access to preventive care. Racial and ethnic minorities frequently experience poorer health outcomes and encounter systemic biases in medical treatment, while rural populations report limited access to healthcare services. The review underscores the need for policy interventions to address structural inequalities in healthcare. Future research should focus on developing targeted interventions to mitigate health disparities across diverse populations and healthcare settings.